Movement and Agreement in Right‐Node‐Raising Constructions. (6th January 2015) - Grosz, Patrick Georg
Abstract This paper discusses the following type of right‐node‐raising construction (Ross 1967): Coordinate structures in which elements that are interpreted in only one conjunct have moved across material that is interpreted as part of both conjuncts. I show that there are constructions of this type that simultaneously exhibit noncanonical plural agreement with two singular DPs and a ban on collective predicates in the same environment, which suggests contradictory conclusions. I argue that these properties follow from an approach to right‐node raising that allows multiple instances of sharing within the same tree (see Gračanin‐Yuksek 2007, 2013; de Vries 2009). I propose an analysis of such plural agreement that treats it on analogy with agreement with conjoined singular DPs. I argue that, for the constructions with noncanonical plural agreement that I discuss, the present analysis is superior over a backward‐deletion analysis and a (non‐multidominance‐based) across‐the‐board movement analysis.